Drivers of degree of sophistication in hotel revenue management decision support systems. (May 2019) - Xu, Xun; Zhang, Lizao; Baker, Tim; Harrington, Robert J.; Marlowe, Byron
Highlights: We develop an internally valid measure of RM sophistication using a decision tree. We show external validity of our hotel RM sophistication measure. We create a new external driver of RM sophistication called eWOM. We show that five external drivers are associated with higher RM sophistication. Abstract: Revenue management (RM) practices enhance financial performance of businesses. This study answers two research questions: (a) How should the sophistication of hotel RM be measured? and (b) What are the internal and external indirect drivers of the level of sophistication of hotel RM? The level of sophistication is based on decision tree tests, which include four steps: data capture, data foundation, rigor of analysis, and techniques used, including pricing, inventory allocation, and product configuration. Via an empirical analysis, we determine five positive drivers of hotel RM sophistication: electronic word-of-mouth utilization, customer segmentation, organizational structure, differentiation strategy, and competitive environment. Our study provides hoteliers with guidelines for determining whether their RM system is at the right level of sophistication given their operating environment, and provides a roadmap for hotels to enhance RM sophistication through efforts to improve both internal and external drivers.